Comparative analysis of acrylonitrile butadiene styrene and polylactic acid samples’ mechanical properties printed in vacuum - Maidin, Shajahan; Md Nor Hayati, Norilani; Rajendran, Thavinnesh Kumar; Muhammad, Ahmad Hilmi (Elsevier B.V., 2023)
This paper presents the findings on the application of a vacuum on an open-source material extrusion system to investigate the effect on the compressive strength and microstructure on the acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA) samples. In addition an infrared spectroscopy analysis was also conducted on the printed samples. The compressive strength was compared to investigate the differences between the findings obtained for the samples printed under vacuum pressure and the results obtained under normal atmospheric pressure. Thus, a vacuum chamber was designed, built, and used to completely confine the printer. Vacuum pressure was maintained at 40kPa during the samples printing process. The printing process parameters include layer thickness of 0.25 mm and 0.40 mm, nozzle temperature of 215 ◦C, heated bed temperature of 90 ◦C, and printed in Z-axis orientation. The samples with a dimension of 12.7 mm in diameter and 25.4 mm in height were printed. The result shows that the overall compressive strength in ABS and PLA for both 0.25 mm and 0.40 mm layer heights, printed with vacuum pressure, shows better compressive strength than printing at atmospheric pressure. For the ABS samples, with a layer height of 0.25 mm, utilizing the vacuum system, the sample’s compressive strength marginally increased by 13.80 %. For the layer height of 0.4 mm, the sample’s compressive strength increased by 9.15 %. For the PLA samples, with a layer height of 0.25 mm, utilizing the vacuum system, the sample’s compressive strength also marginally increased by 7.04 %. For the layer height of 0.4 mm, the sample’s compressive strength increased by 6.27 %. The microstructure analysis shows that both ABS and PLA at atmospheric pressure have a few uneven surfaces. The samples with vacuum pressure, however, showed a smoother and flatter surface. As a result, the quality of both ABS and PLA samples is acceptable and is comparable to the difference reflected in the compressive strength value. After being analyzed by infrared spectroscopy, it has been determined that both ABS and PLA undergo molecular orientation related to crystallinity decrease when printed under vacuum pressure.